Perfil dos escritórios de projetos em organizações atuantes no Brasil - Barcaui, André Baptista (2007)
With the growing awareness of the benefits of project management practices, innovative solutions have been researched and introduced to maintain this way of work in organizations. Its main objective is the continuous improvement of project management, within an environment where restrictions and variables of different sources can be verified. One such solution aimed at the improvement of this environment is an entity known as Project Management Office (PMO). This concept is becoming more and more widespread, both in business and in the academic field, although often without adequate information/clarity regarding the course of action, the PMO implementations in Brazil are a good case in point. This study/research endeavours to understand and analyze this case - the PMO functions, its place within the organization, associated metrics, allocated professionals, and several other aspects of this structure created to promote the project management culture.